Acene‐Modified Small‐Molecule Donors for Organic Photovoltaics. Issue 53 (20th August 2019) - Sung, Min Jae; Hong, Jisu; Cha, Hyojung; Jiang, Yifei; Park, Chan Eon; Durrant, James R.; An, Tae Kyu; Kwon, Soon‐Ki; Kim, Yun‐Hi
Abstract: Invited for the cover of this issue is the group of Tae Kyu An at the Korea National University of Transportation, Soon‐Ki Kwon and Yun‐Hi Kim at the Gyeongsang National University. The image depicts organic photovoltaics, in which fused acene cores have been used to modulate the conjugation lengths and the bulk heterojunction morphologies. Read the full text of the article at 10.1002/chem.201902177 . Abstract : " The promising power conversion efficiencies achieved from the easily synthesized acene‐based small molecules and easy control of bulk heterojunction morphologies suggest that acene‐based small molecules can be useful materials in organic photovoltaics ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 12316 ff. (DOI: 10.1002/chem.201902177 ).